Implementasi Bimbingan Konseling Islami Dalam Upaya Peningkatan Prestasi Belajar Peserta Didik Pada Mata Pelajaran Pendidikan Agama Islam Di Sekolah Menegah Pertama Ciledug Al Musaddadiyah Garut - Raito, Raito; Rahayu, Adnina (STAI Al-Musaddadiyah Garut, 2025)
The development of the young Muslim generation which is starting to enter the teenage phase is a transition period between childhood and adulthood which is marked by significant physical, cognitive, social and emotional changes. Often they are anxious, emotionally unstable, try to rebel, and have minimal understanding of their identity as Muslims. To build good character, a healthy mentality, and help students understand how to apply religious ethical values, Islamic counseling is the right answer to guide them. The aim of implementing Islamic counseling guidance in an institution is that counselors (BK teachers) will help direct and help counselees (students) achieve spiritual, moral aspects and improve learning achievement, especially in Islamic religious education (PAI) subjects. PAI subjects are of course very useful for Indonesia, which is predominantly Muslim because it contains unchanging Islamic teachings, which are sourced from the Al-Qur'an and Hadith. These guidelines teach how students can achieve kaffah Muslims or become pure human beings. This research is a type of research that has a series of scientific activities in order to solve a problem. The method used in this research is a qualitative research method whose research procedures produce descriptive data in the form of written or spoken words from people and observable behavior. This approach is based on the Ciledug Al-Musaddadiyah Middle School in Garut, which has long implemented counseling guidance with an Islamic approach. Based on the research results, it can be concluded that the Islamic counseling guidance implemented at Ciledug al-Musaddadiyah Middle School, Garut, can be implemented well in an effort to increase student learning achievement in PAI subjects in accordance with the types of achievement proposed by Bloom, namely the cognitive side, affective, and psychomotor. This is proven by increasing students' spirituality, learning motivation, and practice. Keywords: Islamic guidance and counseling, learning achievement, Islamic Religious Education subjects.